2016
DOI: 10.3208/jgssp.jpn-094
|View full text |Cite
|
Sign up to set email alerts
|

Stability evaluation for the caisson-type composite breakwater under tsunami condition

Abstract: In order to investigate the instability mechanism of caisson-type composite breakwater under tsunami condition, a scale of 1/100 model experiment was performed in laboratory. Loading tests were also carried out to investigate the reduction of bearing capacity under the existence of seepage flow. From the results of laboratory experiment and finite element analysis, it was confirmed that the bearing capacity of rubble-mound can considerably decrease due to the tsunami-induced seepage flow. It is concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This means that scouring of the rubble mound and the foundation ground is connected to breakwater instability, and strong wave forces finally cause the tilting/overturning of the caisson type breakwater. Moreover, it was revealed that seepage flow in the rubble mound results in the decrease of bearing capacity of rubble mound (Kasama et al 2014). Therefore, it is important to consider the combined effect of scouring, seepage, wave force, and resulting decrease of bearing capacity of breakwater foundation in a comprehensive way.…”
Section: Introductionmentioning
confidence: 99%
“…This means that scouring of the rubble mound and the foundation ground is connected to breakwater instability, and strong wave forces finally cause the tilting/overturning of the caisson type breakwater. Moreover, it was revealed that seepage flow in the rubble mound results in the decrease of bearing capacity of rubble mound (Kasama et al 2014). Therefore, it is important to consider the combined effect of scouring, seepage, wave force, and resulting decrease of bearing capacity of breakwater foundation in a comprehensive way.…”
Section: Introductionmentioning
confidence: 99%